2018
DOI: 10.13102/sociobiology.v65i4.3395
|View full text |Cite
|
Sign up to set email alerts
|

Does Seasonality Affect the Nest Productivity, Body Size, and Food Niche of Tetrapedia curvitarsis Friese (Apidae, Tetrapediini)?

Abstract: Tetrapedia curvitarsis Friese is a widely distributed species, frequently attracted by trap-nests. Previous studies have revealed a higher frequency of nesting in the wet season and dimorphism between the sexes, with females exhibiting larger body size than males. We evaluated the effects of seasonality on the production of nests, food niche, and body size of T. curvitarsis. The study was conducted from April 2009 to March 2010 and from April 2012 to March 2013 at the Água Limpa Experimental Station, located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…A seasonal nesting activity in P. denticulatum was found in those previous studies (Camillo et al, 1996;Ribeiro & Garófalo, 2010). This seasonal pattern has been reported in other wasps, such as Trypoxylon aurifrons (Santoni & Del Lama, 2007), but not in bees as Tetrapedia curvitarsis Friese (Campos et al, 2018). Low nesting activity in the cold and dry period has also been previously reported by Camillo et al (1996) and Camillo (2001).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A seasonal nesting activity in P. denticulatum was found in those previous studies (Camillo et al, 1996;Ribeiro & Garófalo, 2010). This seasonal pattern has been reported in other wasps, such as Trypoxylon aurifrons (Santoni & Del Lama, 2007), but not in bees as Tetrapedia curvitarsis Friese (Campos et al, 2018). Low nesting activity in the cold and dry period has also been previously reported by Camillo et al (1996) and Camillo (2001).…”
Section: Discussionsupporting
confidence: 77%
“…This is an expected finding since size variation in insects are related to quantity and quality of the resources provided to the brood in the larval stage (Peruquetti, 2003;Campos et al, 2018). So, the higher wing size variation may reflect the differential offer of food resources at each environment, as the supply dynamics certainly vary temporally in different phytophysiognomies (Campos et al, 2018). Alternatively, this variation may be associated rather to differential responses of these populations to the features of their local environments (Grassi-Sella et al, 2018), or to local variations in landscape elements (Ribeiro et al, 2019), and specially, to higher developmental constraints to shape than to size variation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The variations found in wing size may reflect the different ways in which floral resources are offered in each environment, since the dynamics of this supply may vary temporally in each phytophysiognomy, associated with variables such as pluviosity and temperature (Morellato et al, 2000;Conceição et al, 2007). Campos et al (2018) observed seasonal variation in the size of males and females of Tetrapedia curvitarsis Friese, 1899, which would be related to the amount of resources stored in brood cells in different seasons.…”
Section: Discussionmentioning
confidence: 95%
“…Wing size showed significant variations between populations from the Atlantic Forest (DMF and DSF), with Caatinga (ARC), Semideciduos Seasonal Forest (SSF) and Savanna (SAV) populations. In insects, size variations are related to quality and quantity of resources provided in larval stage (Peruquetti, 2003;Campos et al, 2018). The variations found in wing size may reflect the different ways in which floral resources are offered in each environment, since the dynamics of this supply may vary temporally in each phytophysiognomy, associated with variables such as pluviosity and temperature (Morellato et al, 2000;Conceição et al, 2007).…”
Section: Discussionmentioning
confidence: 99%